Upaya Penanggulangan Pelecehan Seksual Terhadap Anak Pada Masa Pandemi Covid-19 di Pekanbaru - Heni Susanti; Adip Humaidi (UNES Law Review, 2023)
This study aims to determine the implementation of the investigation carried out by the PPA Unit of the Riau Police of Pekanbaru during the Covid-19 Pandemic in the crime of sexual abuse of children and the efforts made by the PPA Unit of the Riau Police of Pekanbaru during the Covid-19 Pandemic in tackling the crime of sexual harassment. against children. This type of research uses empirical legal research methods carried out by the PPA Unit of the Riau Police Pekanbaru. The data obtained is primary data by using interview techniques with the head of the PPA Unit Polda Riau Pekanbaru. The data obtained were analyzed qualitatively using deductive methods, and then presented descriptively. The results of the research obtained are that the investigation carried out by the PPA Unit of the Riau Police of Pekanbaru in the crime of sexual abuse of children during the Covid-19 Pandemic is by conducting an investigation in accordance with applicable legal rules and carried out with the principle of systematic law enforcement. In addition to this, the PPA Unit of the Riau Police of Pekanbaru coordinates and cooperates in investigations with several relevant stakeholders with criminal acts of sexual abuse against children during the Covid-19 Pandemic. With the efforts made by the PPA Unit Polda Riau Pekanbaru in tackling the crime of sexual abuse against children is a preemptive effort, namely by giving an appeal with an approach to the community against the dangers that arise in sexual abuse of children. The next effort is a preventive effort by means of supervision and prevention by conducting routine patrols during the day and also at night by collecting data, and the last effort is a repressive effort by means of law enforcement related to the crime of sexual abuse of children.